SIGNATURE PSO: MODIFIED PARTICLE SWARM OPTIMIZATION DENGAN FUZZY SIGNATURE DAN IMPLEMENTASI PADA OPTIMALISASI KENDALI LQR - Novendra Setyawan; Ermanu Azizul Hakim; Zulfatman Zulfatman (MULTITEK INDONESIA, 2020)
Particle Swarm Optimization (PSO) is an optimization that is simple and reliable to complete optimization. In this method, the distribution of particles through global search and local search is the key obtained through searching with PSO through the inertia parameter. This paper describes the method of changing the weights on PSO using fuzzy signatures. In this paper, the method used to solve the problem of optimizing the LQR control parameters on the stabilization of a double inverted pendulum. Performance evaluation is done by another weight change algorithm. Integral Time Absolute Error (ITAE) 7% compared to other algorithms. PSO signatures have resilience and are optimal in fulfilling these interests.